THERAPEUTIC POTENTIAL OF SCORPION VENOM IN CANCER TREATMENT AS ANTICANCER AGENT: A REVIEW (Journal of Forensic Medicine & Toxicology, 2022)
Scorpions are distinguished via their deadly stings, which could give result in serious repercussions for humans. It is the most expensive fluid in the planet, costing $39 million per gallon. Cancer is a very frequent disease nowadays. This causes aberrant cell growth, which has the potential to infect or spread to other regions of the body. The presence of 42 multipart cocktail of biogenic amines, proteins, organic salts, mucoproteins, peptides, and 43 neurotoxins in scorpion venom has proven a prospective therapeutic application on cancer cells in medical research. Furthermore, an increasing number of research have suggested that scorpion venoms and poisons may inhibit cancer growth, limit cancer development and metastasis, and promote cancer remission. induce apoptosis and in vitro and in vivo.
Keywords: Scorpion; Cancer; Therapeutics; Pharmacological